Community based mount Merapi eruption disaster management - Permana, Septian Aji; Hartanto, Supri; Purwatiningsih, Ary; Magiman, Mohamad Maulana (Hamdard National Foundation, 2020)
Purpose -This research purpose is to analyze society management in manage natural resource that gotten from Merapi eruption and fin ding the economical system based on regional autonomy. Design/methodology/approach -This research used qualitative approach. The informant of this research was Cangkringan society, Cangkringan village employee, and investors. Data collecting technique was done by observation patricianly and structural interview. Data then analyzed by domain analysis technique, taxonomic, competence, and cultural theme. Findings -The research result shows that Cangkringan society has local wisdom in manage economic after Merapi disaster by opening business entity like cooperative. Social implications -The purpose of Cooperative is to give fund to the Cangkringan society to make them become independent and not dependent to foreign investor. With this cooperative, society can manage economic independently based on local wisdom. Originality/value -Cooperative is business entity that manages by society to their own welfare (from society to society).